Miselni modeli cepljenja, zaupanje v zdravstvo in odnos staršev do cepljenja otrok - Gjorgjievski, Bojan (Psihološka obzorja (Ljubljana), 2016)
Many contradictory notions have been appearing in the area of health care in recent years, including those related to attitudes towards vaccination. On the basis of their understanding of the phenomenon some parents oppose to the vaccination. The purpose of this study was to compare mental models of laymen with expert models and examine the correlation of the mental models of vaccination and the trust in doctors and healthcare system with the parental attitudes on childhood vaccination. In doing so, we have considered the demographic characteristics of the parents and cultural differences between parents from Slovenia and Macedonia. We were also interested in the role of compulsory and optional vaccination, because in the latter the behavioral intention is expressed more clearly. The methods used in our study of mental models was based on the approach of Morgan, Fischhoff, Bostrom and Atman (2002) which has three phases: (1) obtaining expert mental models, (2) getting mental models of the laymen (e.g., parents) and (3) comparison of both mental models. Expert models of vaccination were obtained from five doctors from Slovenia and five doctors from Macedonia. Laymen models of vaccination were obtained in structured interviews with 33 parents from Slovenia and 30 from Macedonia. Based on comparisons of expert and lay mental models it can be concluded that the mental models of vaccination from parents of one-year old children differ from expert mental models. Most parents, both Macedonian and Slovenian, have also responded that they have greater confidence in the doctors rather than the healthcare system, mainly due to positive experiences with the selected pediatrician. In some Slovenian parents, a tendency to identify compulsory vaccination with force was noticed.
Keywords: cepljenje; vaccination; mental models; miselni modeli; parents; starši; attitudes; stališča; trust; zaupanje; zdravniki; doctors; Slovenia; Slovenija; Macedonia; Makedonija; Republic of Macedonia; medkulturne razlike; cross cultural differences